2009
DOI: 10.17221/940-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Content of Bioactive Components in Chosen Cultivars of Cranberries (Vaccinium vitis-idaea L.)

Abstract: Abstract:The of relation between chosen macro-and microelements, total polyphenol (TP) and anthocyanin content (TA) and antioxidant capacity (TAC) in 6 selected cultivars of cranberries (Sussi, Linnea, Sanna, Runo Bielawski, Ida, Koralle) is the aim of this study. The influence of cultivars on macro-and microelements content was confirmed. The Mg content was in interval 478.3-555.2 mg/kg, K 5690-7690 mg/kg, Fe 10.7-29.3 mg/kg, Cr 0.5-0.8 mg/kg, Cu 3.5-5.0 mg/kg and Zn 8.1-9.8 mg/kg. The lowest Mg, Cr, and Cu c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Total nine flavonoids (rutin, myricetin, morin, quercetin, kaempferol, catechin, naringin, naringenin) are studied in this study (Table 4). Artemisia species generally known as rich antioxidant sources such as flavonoids, coumarins [24,30]. It is found that all studied species apart from A. vulgaris posses highest catechin content (3288.8-9877.6 µg/g) in the present study.…”
Section: Flavonoid Contents and Radical Scavenging Activities Of Artesupporting
confidence: 48%
“…Total nine flavonoids (rutin, myricetin, morin, quercetin, kaempferol, catechin, naringin, naringenin) are studied in this study (Table 4). Artemisia species generally known as rich antioxidant sources such as flavonoids, coumarins [24,30]. It is found that all studied species apart from A. vulgaris posses highest catechin content (3288.8-9877.6 µg/g) in the present study.…”
Section: Flavonoid Contents and Radical Scavenging Activities Of Artesupporting
confidence: 48%
“…Pan, Jiang, and Pan (2011) found rapeseed protein hydrolysates to be a potential source of antioxidants in addition to high quality protein for human consumption. The antioxidant compounds in selected fruits or berry and vegetables and their products are listed in Tables 3 and 4 (Heinonen, Ollilainen, Linkola, Varo, & Koivistoinen, 1989;Plumb, Chambers, Lambert, Wanigatunga, & Williamson, 1997;Hollman & Arts, 2000;Hussein et al, 2000;van den Berg et al, 2000;Matilla, Suanpa, & Piironea, 2000;Chuanphongpanich, Suttajit, Phanichphant, Buddhasukh, & Slrlthunyalug, 2006;Sorensen et al, 2001;Ewald, Fjelkner-Modig, Johansson, Sjoholm, & Akesson, 1999;Mohammed, 2002;Clifford, 2000;Rao & Kiran, 2011;Hertog, Hollman, & Katan, 1992;Lees, Wall, Beveridge, & Suttill, 1995;Kahkonen, Hopia, & Heinonen, 2001;Hakkinen, Karenlampi, Mykkanen, & Torronen, 2000; IJFS April 2013 Volume 2 pages 81-104 Meyer, Currie et al, 2006;Miller & RiceEvans, 1997;Risch & Herrmann, 1988;Macheix, Fleuriet, & Billot, 1990;Kalt, Forney, Martin, & Prior, 1999;Vollmannova et al, 2009;Lees & Francis, 1972;SaperS, Phillips, Rudolf, & Divito, 1983;Sapers, Jones, & Maher, 1983;Billyk & Sapers, 1986;Santos-Buelga & Scalbert, 2000;Mullen, Marks, & Crozier, 2007;Stohr & Herrmann, 1975;Chang, Tan, Frank...…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Pan, Jiang, and Pan (2011) found rapeseed protein hydrolysates to be a potential source of antioxidants in addition to high quality protein for human consumption. The antioxidant compounds in selected fruits or berry and vegetables and their products are listed in Tables 3 and 4 (Heinonen, Ollilainen, Linkola, Varo, & Koivistoinen, 1989;Plumb, Chambers, Lambert, Wanigatunga, & Williamson, 1997;Hollman & Arts, 2000;Hussein et al, 2000;van den Berg et al, 2000;Matilla, Suanpa, & Piironea, 2000;Chuanphongpanich, Suttajit, Phanichphant, Buddhasukh, & Slrlthunyalug, 2006;Sorensen et al, 2001;Ewald, Fjelkner-Modig, Johansson, Sjoholm, & Akesson, 1999;Mohammed, 2002;Clifford, 2000;Rao & Kiran, 2011;Hertog, Hollman, & Katan, 1992;Lees, Wall, Beveridge, & Suttill, 1995;Kahkonen, Hopia, & Heinonen, 2001;Hakkinen, Karenlampi, Mykkanen, & Torronen, 2000; IJFS April 2013 Volume 2 pages 81-104 Meyer, Currie et al, 2006;Miller & RiceEvans, 1997;Risch & Herrmann, 1988;Macheix, Fleuriet, & Billot, 1990;Kalt, Forney, Martin, & Prior, 1999;Vollmannova et al, 2009;Lees & Francis, 1972;SaperS, Phillips, Rudolf, & Divito, 1983;Sapers, Jones, & Maher, 1983;Billyk & Sapers, 1986;Santos-Buelga & Scalbert, 2000;Mullen, Marks, & Crozier, 2007;Stohr & Herrmann, 1975;Chang, Tan, Frank...…”
Section: Natural Antioxidantsmentioning
confidence: 99%